2023
DOI: 10.1002/mas.21857
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in mass spectrometry techniques for atmospheric chemistry research on molecular‐level

Abstract: The Earth's atmosphere is composed of an enormous variety of chemical species associated with trace gases and aerosol particles whose composition and chemistry have critical impacts on the Earth's climate, air quality, and human health. Mass spectrometry analysis as a powerful and popular analytical technique has been widely developed and applied in atmospheric chemistry for decades. Mass spectrometry allows for effective detection, identification, and quantification of a broad range of organic and inorganic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 352 publications
1
8
0
Order By: Relevance
“…Based on recent developments of high-resolution mass spectrometry techniques, several recent studies reported molecular-level identification of particle-phase organic peroxides. , However, these mostly rely on tentative formula assignment as the method of identification, while unambiguous assignments are only possible when authentic standards are available. For the first time with the help of AAHP standards, we unambiguously identified four AAHPs and quantitative estimates are given for two types of monoterpene-SOA generated in a laboratory flowtube reactor.…”
Section: Resultsmentioning
confidence: 99%
“…Based on recent developments of high-resolution mass spectrometry techniques, several recent studies reported molecular-level identification of particle-phase organic peroxides. , However, these mostly rely on tentative formula assignment as the method of identification, while unambiguous assignments are only possible when authentic standards are available. For the first time with the help of AAHP standards, we unambiguously identified four AAHPs and quantitative estimates are given for two types of monoterpene-SOA generated in a laboratory flowtube reactor.…”
Section: Resultsmentioning
confidence: 99%
“…Mass spectrometry represents a nearly universal method for determining the chemical composition of organic and inorganic species across various environmental matrices. In the fields of environmental and atmospheric chemistry, chemical ionization (CI) is a versatile real-time method to measure individual organic and inorganic compounds in air at trace concentrations (Yuan et al, 2017;Riva et al, 2019;Zhang W. et al, 2023;Zhang Y. et al, 2023). As in all chemical ionization systems, trace analytes in air react with excess reagent ions, leading to the formation of charged product ions usually via electron/proton transfer or adduct formation (Zhang W. et al, 2023;Zhang Y. et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In the fields of environmental and atmospheric chemistry, chemical ionization (CI) is a versatile real-time method to measure individual organic and inorganic compounds in air at trace concentrations (Yuan et al, 2017;Riva et al, 2019;Zhang W. et al, 2023;Zhang Y. et al, 2023). As in all chemical ionization systems, trace analytes in air react with excess reagent ions, leading to the formation of charged product ions usually via electron/proton transfer or adduct formation (Zhang W. et al, 2023;Zhang Y. et al, 2023). Advances in the field of chemical ionization over the last decade have yielded exceptionally low detection limits down to 10 4 molecules cm -3 (part-per-quadrillion), expanded dynamic ranges, and the capability of measuring a wide range of gaseous organic and inorganic species with time resolutions of up to 50 Hz (Riva et al, 2019;Zhang W. et al, 2023;Zhang Y. et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations